Determinan Perilaku Merokok Remaja Berdasarkan Komponen Health Belief Model: Kajian Literatur - Muhammad Luthfi Tsanyan (Barongko: Jurnal Ilmu Kesehatan, 2026)
Smoking behavior among adolescents is a growing public health problem with a high potential to increase the risk of non-communicable diseases in the future. The high number of adolescent smokers in Indonesia indicates the need for a deeper understanding of the individual factors that influence this behavior. This study aims to analyze individual factors in adolescent smoking behavior using the Health Belief Model (HBM) theory. The method used is a literature review of relevant national and international journals, taken from the Google Scholar and PubMed databases. This study was conducted from October to December 2025 by evaluating various studies on adolescent smoking behavior and aspects of HBM. The findings of this study reveal that smoking behavior in adolescents is influenced by perceptions of vulnerability, perceptions of severity, perceived benefits, perceived barriers, and self-efficacy. Although many adolescents are aware of the dangers of smoking, this does not encourage them to take preventive measures or quit smoking. Social and psychological barriers, as well as addiction levels, are factors that hinder behavioral change, while self-efficacy plays a key role in adolescents' ability to refuse or quit smoking. In conclusion, adolescent smoking behavior is more influenced by how individuals interpret risks and beliefs about health than by knowledge alone. Therefore, health promotion interventions must strengthen all components of the HBM comprehensively.